2003
DOI: 10.1212/01.wnl.0000068549.52812.0f
|View full text |Cite
|
Sign up to set email alerts
|

Idebenone treatment in Friedreich’s ataxia

Abstract: The authors report 1-year prospective data on eight patients with Friedreich ataxia. Idebenone did not halt the progression of ataxia. At the end of therapy, cardiac ultrasound demonstrated significant reduction of cardiac hypertrophy in six of eight patients. Cardiac strain and strain rate imaging showed that the reduction of hypertrophy is preceded by an early and linear improvement in cardiac function. Idebenone reduced erythrocyte protoporphyrin IX levels in five of six patients with elevated baseline leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(87 citation statements)
references
References 8 publications
5
80
0
2
Order By: Relevance
“…In contrast, use of idebenone was associated with younger age, shorter GAA repeat length and cardiomyopathy. Several studies suggest that idebenone may be efficacious in young patients with cardiomyopathy, and the dose used here by FA patients roughly matches that used in European trials (7,9,10), suggesting that the use of idebenone in part reflects reading of the medical literature by physicians and families. The association of idebenone use with shorter GAA repeat length when age is controlled likely reflects the subpopulation of adults with late onset disease that are more readily capable of obtaining idebenone.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, use of idebenone was associated with younger age, shorter GAA repeat length and cardiomyopathy. Several studies suggest that idebenone may be efficacious in young patients with cardiomyopathy, and the dose used here by FA patients roughly matches that used in European trials (7,9,10), suggesting that the use of idebenone in part reflects reading of the medical literature by physicians and families. The association of idebenone use with shorter GAA repeat length when age is controlled likely reflects the subpopulation of adults with late onset disease that are more readily capable of obtaining idebenone.…”
Section: Discussionmentioning
confidence: 56%
“…Since modest longitudinal motor skill improvements can be perceived only under conditions of sufficient muscle force (corrected for longitudinally increasing normative age and weight standards), ICARS could become dependent upon muscle force. In accordance with a potentially modest effect of idebenone upon cardiomyopathy, 23 we cannot, therefore, exclude the possibility that idebenone could exert some beneficial effect by sustaining activity levels and ⁄ or (cardiac) muscle stabilization.…”
Section: Discussionmentioning
confidence: 95%
“…Since modest longitudinal motor skill improvements can be perceived only under conditions of sufficient muscle force (corrected for longitudinally increasing normative age and weight standards), ICARS could become dependent upon muscle force. In accordance with a potentially modest effect of idebenone upon cardiomyopathy, 23 we cannot, therefore, exclude the possibility that idebenone could exert some beneficial effect by sustaining activity levels and ⁄ or (cardiac) muscle stabilization.In the absence of SEPs, the presented association between muscle weakness and ICARS leg subscores in children with FRDA can be understood by the concept that execution of ICARS requires a minimum level of muscle force (for contractions against gravity and maintenance of the upright body position). As a result, FRDA muscle weakness would first affect the ICARS scores of the most paretic muscles.…”
mentioning
confidence: 95%
“…Another study found that six (among eight) patients with FRDA exhibited an important reduction of cardiac hypertrophy (119), although no improvement in ataxia was noticed in any of these trials.…”
Section: Spinocerebellar Atrophiesmentioning
confidence: 93%